A STUDY ON THE IMPLEMENTATION OF SHORT STORIES IN TEACHING READING COMPREHENSION - Mulya Sari, Ika; Mukrim, Mukrim; Anggreni, Afrillia; Dewi, Anjar Kusuma (Tadulako University, 2025)
This research is to analyze short stories in teaching reading comprehension. This study was aimed at benefiting these readily used materials to improve the eighth graders’ reading comprehension of narrative texts. The study applied action research design since it opens the opportunity for teachers-practitioners to be involved in research. Based on the results of the students’ tests as well as their on-going assessments, it is found out that the students’ reading comprehension was gradually improving. It means that there was a positive effect of using Online Short Stories towards the students’ reading ability. The result shows that the combination of materials and worksheets that were implemented in both cooperative and individual learning had facilitated the students in improving their reading comprehension ability, as well as their social skills. Therefore, it is very important to implement this strategy to order to improve the students’ reading comprehension.